An Analysis of Performance of Agro-Based Industries in Kerala with Special Reference to Coconut - Vinitha K. (Dept of Economics, MES Mampad College, 2019)
Coconut is one of the major crops in Kerala which has multifaceted uses. Coconut and coconut products play a vital role in contributing health and nutrition globally. As per the All India estimates for the year 2016-17, the area and production of coconut in the country is 2.096 million hectares and 22237.97 million nuts respectively. Coconut processing units were working under the Coconut development Board for producing various coconut products. Around 30 units were assisted during 2016-17 and the board has sanctioned the establishment of 22 processing units in the country during 2017-18.There are traditional coconut products and non-traditional coconut products. The coconut processing industry plays a significant role in Kerala’s economy in terms of foreign exchange earnings and as an employment. The present study mainly focused on the performance of coconut industries in Kerala and also made an attempt to understand the reasons behind the reduction of production and exports in the state.The present study relies entirely on secondary data. The data has been collected from various sources like economic review, sites of CDB, Indian Coconut Journal and various other journals.The production and export of coconut industries in Kerala exhibit declining trend.